FROM LOGBOOKS TO logBlog: AN EXPLORATORY STUDY OF DIGITAL DOCUMENTATION IN INDUSTRIAL TRAINING - Khairul Adilah Ahmad; Sharunizam Shari; Anis Faradella Abdul Malik; Ahmad Afif Ahmarofi; Chantorn Chaiprasurt (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This exploratory study investigates the use of logBlog, a digital platform created with Google Sites, as a modern alternative to traditional logbooks in industrial training. The study’s primary objective is to determine whether multimedia-rich digital platforms can overcome the limitations of traditional, text-based logbooks, which struggle to fully capture the complexity and variety of modern industrial training experiences. By allowing students to incorporate multimedia elements such as images, videos, and audio, logBlog offers a more dynamic and comprehensive method of documenting learning experiences. This study aims to explore how this approach can improve student engagement, reflection, and real-time communication with supervisors. The methodology employed in the study is primarily conceptual, focusing on theoretical analysis. It evaluates how logBlog enhances the documentation process through multimedia integration, allowing for deeper, more meaningful reflections on students’ training experiences. The paper also identifies key challenges associated with adopting digital documentation tools, such as the need for digital literacy, potential resistance to change from both students and supervisors, and concerns over privacy and security in handling sensitive data during industrial training. These challenges form part of the critical analysis of the platform’s effectiveness and broader adoption in educational settings. The results suggest that logBlog offers significant improvements over traditional logbooks by fostering increased student engagement, deeper reflection, and improved real-time feedback from supervisors. However, overcoming the technical barriers, ensuring the necessary infrastructure, and addressing concerns regarding data privacy remain critical to its successful adoption. The significance of the study lies in its potential contribution to the modernization of documentation practices in industrial training. By leveraging digital tools, logBlog can enhance learning outcomes and contribute to the ongoing digital transformation in education. The paper highlights the need for future research to evaluate the platform’s scalability, real-world effectiveness, and security in diverse training environments.